Exploration of sodium homeostasis and pharmacokinetics in bile duct-ligated rats treated by anti-cirrhosis herbal formula plus spironolactone - Hsueh, Tun-Pin; Tsai, Tung-Hu (Frontiers in Pharmacology, 2023)
Renal sodium retention is an essential indicator that is used for the prognosis of cirrhosis with ascites that requires diuretic treatment to restore sodium homeostasis. The diuretic effects of Yin-Chen-Hao-Tang (YCHT) alone or in combination with diuretics for sodium retention in patients with cirrhosis have not been investigated. This study aimed to investigate the diuretic effect and sodium retention caused by YCHT with spironolactone, from both the pharmacokinetic and pharmacodynamic perspective, in bile-duct ligated rats. The HPLC method was validated and utilized for the pharmacokinetic analysis of rat urine. Urine samples were collected and analyzed every four hours for 32 h after oral administration of YCHT at 1 or 3 g/kg daily for 5 days in bile-duct ligated rats. A dose of 20 mg/kg spironolactone was also administered to pretreat the YCHT 1 g/kg or the 3 g/kg group on the 5th day to explore the interaction of the two treatments. Urine sodium, potassium, weight, volume, and spironolactone and canrenone levels were measured to investigate fluid homeostasis after coadministration. The linearity, precision, and accuracy of the HPLC method were suitable for subsequent urinary pharmacokinetic analyses. The pharmacokinetic parameters in the 1 g/kg YCHT with spironolactone group revealed that the elimination half-life of the spironolactone metabolite, canrenone, was prolonged. In addition, the cumulative excretion amount, the area under the rate curve (AURC), and the maximum rate of excretion (Rmax) were significantly decreased when spironolactone group was pretreated with 3 g/kg YCHT. Urinary sodium excretion elicited by spironolactone was suppressed by pretreatment with 1 or 3 g/kg YCHT. 32-hour urine output was not altered by the administration of YCHT alone, but it was significantly decreased by 64.9% after coadministration of YCHT with spironolactone. The interaction of spironolactone and YCHT was found to decrease urine sodium-potassium and water excretion, and this change was attributed to the decreased level of spironolactone metabolites and possibly the regulation of the renin-angiotensin-aldosterone system by obstructed cirrhosis. Dose adjustment of YCHT or diuresis monitoring should be noted when co-administering YCHT and spironolactone to treat hepatic diseases clinically.